“Caracterización del sector agrícola y la generación de emprendimientos en las empresas- grupos económicos del cantón La maná, año 2020. - Bustamante Ochoa, Leylis Eliana (2021)
The agricultural sector is a subsector that is integrated within the primary sector, this is composed of those activities that comprise the agricultural sector, or the practice in the field, in other words, it is nothing more than the union of two subsectors that are part of the primary sector, it includes all activities related to agriculture, due to its relevance are classified in this way, receiving the name of agricultural sector. The agricultural sector produces fruit and vegetable crops, greenhouses and nurseries, activities related to the cultivation of grains and seeds, industrial agriculture, and large-scale agricultural support activities. The inexperienced characterization makes it difficult to undertake and the lack of support from the government makes it even more difficult, the population is 833 companies engaged in agricultural activity in La Maná. The population is 833 companies that carry out agricultural activities in La Maná, which is segmented and its sample corresponds to 270 that were taken as a research study. The general objective is to analyze how the characterization of the agricultural sector affects the generation of enterprises for the economic improvement of the companies - economic groups of La Maná canton, the methodology used were: Theoretical, deductive, analytical, empirical method, are the tools that were used to obtain and analyze the data. Type of research, bibliographic, field, its level or scope was descriptive, correlational, the techniques used were: research techniques, survey, instruments used, questionnaire, the research design is composed of the population and sample, and the distribution of the sample. The most relevant findings show that the indicators with the highest relationship are the variables strategy for product launching (0.753) and market entry barriers (0.719). It is concluded that the characterization of the agricultural sector has an impact on the generation of entrepreneurship in view of the results an entrepreneurship model is planned.